Our experiences and suggestions with PEEK marker use in prostate cancer radiotherapy - Sen, Cenk Ahmet (Contemporary Oncology/Współczesna Onkologia, 2018)
Polyether ether ketone (PEEK), a material commonly used in industry, has recently been introduced in medicine. The use of PEEK in place of gold in gold marker implantation for prostate radiotherapy has been suggested to be advantageous because it is associated with a lower level of artefacts. In this study, we present a disadvantage of this newly introduced method, which has not yet been defined in the literature, and offer a solution for this problem to shed light on this issue, which has not yet been completely understood.